SHAKESPEARE'S INFLUENCE ON ENGLISH LITERATURE: A COMPREHENSIVE EXAMINATION OF THEMES, TECHNIQUES, AND CULTURAL IMPACT (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This extensive article investigates the profound influence of William Shakespeare on English literature, spanning centuries of literary analysis, scholarly debate, and cultural adaptation. Through an interdisciplinary approach, we explore Shakespeare's thematic depth, innovative techniques, and enduring legacy, examining his contributions to drama, poetry, language, and cultural discourse. By delving into the historical context of his works and their ongoing relevance, we illuminate Shakespeare's unique place in the literary canon and his lasting impact on global culture.